2012
DOI: 10.4236/ojst.2012.23032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of removable partial dentures: A retrospective clinical study

Abstract: Removable partial dentures (RPDs) (conventional and implant-supported) treatment is considered a viable option to replace missing teeth as inexpensively as possible, but it has limitations. Objectives: This study reports the effect of gender and location (maxilla vs. mandible) on the clinical performance of removable partial dentures (RPDs). Materials and Methods: A total of 100 Patients who had RPDs delivered between 1990-1995 were evaluated. A 4-point scoring system was used to assess seventeen criteria. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
0
16
0
8
Order By: Relevance
“…8 The role of RPD design in the success of the denture is an accepted fact. 2,21,22 The results of this study showed that 62.5% of the dentists offered no design information when they sent a master model or impression to the laboratory for RPD fabrication. This result is higher than the findings of Kilfeather et al (54%, England, Ireland and Wales), Radhi et al (57%, Bahrain) and Pun et al (42%, Wisconsin, USA).…”
Section: Discussionmentioning
confidence: 86%
“…8 The role of RPD design in the success of the denture is an accepted fact. 2,21,22 The results of this study showed that 62.5% of the dentists offered no design information when they sent a master model or impression to the laboratory for RPD fabrication. This result is higher than the findings of Kilfeather et al (54%, England, Ireland and Wales), Radhi et al (57%, Bahrain) and Pun et al (42%, Wisconsin, USA).…”
Section: Discussionmentioning
confidence: 86%
“…O insucesso pode ser evitado quando realizado uma oroscopia adequada, diagnóstico correto, planejamento adequado, exames clínicos e radiográficos detalhados e moldagem apropriada (4,5).…”
Section: Solução Estética Após Falha De Planejamento Protético I N T unclassified
“…Para Etman (2012) a preparação pré-protética em PPR compreende uma série de procedimentos que objetivam modificar as superfícies dentárias para posterior adaptação da prótese. Dentre os procedimentos inclusos nessa fase temos: remoção de carie e doença periodontal, ajuste do plano oclusal, preparo de nichos, criar áreas retentivas, identificar lesão em tecidos moles, entre outros (5)(6)(7)(8).…”
Section: F I G U R a 6 F I G U R A 7 D I S C U S S ãOunclassified
See 2 more Smart Citations